Bioactive (co)oligoesters with antioxidant properties – synthesis and structural characterization at the molecular level. Issue 62 (15th June 2016) - Maksymiak, Magdalena; Bałakier, Tomasz; Jurczak, Janusz; Kowalczuk, Marek; Adamus, Grazyna
Abstract : Anionic ring opening (co)polymerization of novel β-substituted β-lactones to bioactive (co)oligoesters with antioxidant properties. Abstract : A contemporary synthetic route, starting from the bioactive compound via the corresponding glycidyl ester and β-substituted β-lactone to (homo)- and (co)oligoesters with a bioactive moiety covalently linked as pendent groups along an oligomer backbone, was reported. The bioactive compounds were selected from antioxidants used in cosmetics. Two models of bioactive (homo)- and (co)oligoesters were synthesized via anionic ring-opening (co)oligomerization of p -methoxybenzoyloxymethylpropiolactone ( p -AA-CH2 -PL) initiated by p -anisic acid sodium salt. An analytical protocol was developed for a detailed structural characterization at the molecular level of these bioactive (co)oligoesters. The molecular level structure of the obtained bioactive (homo)- and (co)oligoesters was established by electrospray ionization tandem mass spectrometry (ESI-MS/MS) supported by 1 H NMR analysis. Additionally, the results presented here are important for the analysis of designed biodegradable polymeric controlled-release systems of bioactive compounds with potential applications in cosmetology.